Effet De Prétraitements, De Substrats Et De Stress Hydriques Sur La Germination Et La Croissance Initiale De Diospyros Mespiliformis Hochst. Ex A.DC - Ado, Ali; Bil-Assanou, Issoufou Hassane; Iro, Dan Guimbo; Karim, Toudou Daouada Abdoul; Ali, Mahamane; Mahamane, Saadou (European Scientific Journal, ESJ, 2017)
This study is on the seeding and the initial growth of a food species, Diospyros mespiliformis, in Niger. Diospyros mespiliformis is an overexploited food species in Niger. The aim of this study is to determine the optimal conditions for germination and seedling growth of this species. In doing so, seed germination tests were conducted in petri dishes laboratory and seedling growth survey respectively. Also, the nursery was done using bags. The treatments involve the seed staying in warm water for 1, 3, 5, 7 days; scalding; and mechanical scarification. In the nursery, the substrates used are alluvial soil and alluvial soil mixed in 1/4, 1/3, and 1/2 of organic manure. As a result, the growth monitoring is done on plants kept in the shade. Others were exposed to the sun for 12 months by applying water stress (watering every day; 2 and 1 times per week; and without watering). Thus, the germination capacity is 55, 4% without treatment and it reached 74% by scalding. The conservation makes it reduce to 43% after 6 months and 25% after 1 year. In the nursery, the emergence rate is 52,8 % in alluvial soil, but it reduced to 10% in the substrate (soil 1/2 and 1/2 fertilizers). D. mespiliformis growth is slow during cold weather and becomes fast during hot weather. When the weather is shady or sunny, this species supports four months of drought by developing a significant root system. D. mespilformis can be used for afforestation.